Forme rare de malformation anorectale avec une fistule recto urethrobulbaire: à propos d’un cas - Alaoui, Othmane (Pan Afr Med J, 2017)
We here report the case of a male newborn admitted immediately after birth with imperforate anus. Physical examination of the anal margin showed imperforate anus; the examination of the external genitalia objectified scrotal bifidity with a fistula filled with meconium at the level of the penis root. During urinary catheterization the catheter passed through the fistula (A), suggesting a rare anorectal malformation with recto-uretrobulbar fistula. Malformation assessment was without abnormalities. The newborn was admitted to the operating room and clouding was performed during surgery by catheterization of the fistula using two 6 CH (1.98mm) Foley catheters, one passing through the rectum and the other passing through the bladder; a third foley catheter passed through the urethral meatus, objectifying the communication among the three catheters at the level of the recto-uretrobulbar fistula (B). The diagnosis of rare intermediate anorectal malformation was retained and colostomy was performed. The newborn underwent treatment based on perineal anorectoplasty with fistula closure at the age of 3 months. Anal dilatation was performed for 6 months. Colostomy closure was performed at the age of 9 months. Patient's evolution was favorable at 2-year follow-up.